The potentiality of Citral in targeting breast cancer multicellular tumour spheroids (MTS) - Rusli, Muhammad Ehsan Fitri; Rosli, Rozita; Ramli, Ummu Bar’iah; Ahmad Suhaimi, Shafinah; Saad, Norazalina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: As the high incidence of breast cancer has a profound impact on a global scale, there is a critical need to improve the clinical outcome of the patients, including efforts to utilize bioactive natural products as treatment or preventive measures. Citral, the essential oil of lemongrass has been reported to possess cytotoxicity in breast cancer cell line . The aim of present study was to determine the capability of citral in targeting aldehyde dehydrogenase-positive (ALDH+) cells in breast cancer cells. Methods: Both MCF-7 and MDA-MB-231 cells were cultured in serum-free media to generate multicellular tumour spheroids for the evaluation of citral as an antiproliferative agent. The cells were treated with identified IC50 (50±4.30 µM and 56±3.17 µM of citral, respectively) to investigate the cytotoxicity of citral. Staining using Propidium Iodide (PI) and Hoechst 33342 was carried out to determine cell proliferation and viability. Finally, ALDH+ cells were quantified via ALDEFLUOR assay. Analysis of differences was carried out by analysis of variance (ANOVA) and independent t-test with p<0.05 considered statistically significant. Results: The size of spheroids in both cancer cell lines were reduced after treatment with the citral. PI and Hoechst 33342 staining also revealed that citral gave rise to a mixture of cells that are normal and undergoing apoptosis and necrosis. ALDEFLUOR assay analysis revealed citral significantly (p <0.05 ) inhibited the population of ALDH+ cells in MCF7 cells. Conclusion: It was demonstrated that citral reduced the ALDH+ cell population in MCF7 breast cancer spheroids by inhibiting the ALDH activity.